Application of plant simulation software as a process improvement tool in automotive radio line - Santos, Tatiane Pinto dos; Souza Junior , Armando Araújo de; Silva, Carlos Américo de Souza (Brazilian Journal of Production Engineering, 2024)
Companies should improve their processes to meet consumer demands. Computer simulation is a powerful tool for implementing process improvements, as it provides a virtual representation of a system in different scenarios, aiding decision-making. The study utilized the Plant Simulation program to determine the optimal size of WIPs on an automotive radio assembly line in the Manaus industrial district, considering the Just in Time (JIT) principle of producing only what is necessary. Real data was used to simulate the process, obtained through chrono-analysis of the assembly line workstations and Yamazumi methodology to identify the main losses. After dimensioning the WIPs using the software, they were implemented on the assembly line. The results were positive, including a reduction in machine idleness and a 6% increase in the line’s production capacity.